ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB) PADA KARYAWAN AKADEMI MARITIM NUSANTARA - Andi Hendrawan; Hari Sucahyawati; Indriyani - (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2017)
The objective of this research were to know Organizational Citizenship Behavior (OCB) at AMN employee. Organizational Citizenship Behavior (OCB) as an individual behavior that is discretionary, not directly or explicitly recognized by the formal reward system, and that in the aggregate promotes the effective functioning of the organizationThe excellent performance of demanding "behavior" of employee is expected by the organization. Behavior demanded by today's organizations is not only in-role behavior but also extra-role behavior. Extra-role behavior is also called the Organizational Citizenship Behavior.OCB is a term used to identify the employee behaviors that can be called a "good t employee ". If employee in the organization have OCB, efforts to control taruna declined, since employees can control their own behavior or being able to choose the best behavior for the benefit of the organization The keyword: employee, Organizational Citizenship Behavior (OCB).